Protective Effect of Simplicillium sp. Ethyl Acetate Extract against High Glucose-Induced Oxidative Stress in HUVECs. (17th August 2020) - Tian, Ting-Ting; Li, Qi-Rui; Gan, Shi-Quan; Chang, Chu-Rui; Shen, Xiang-Chun
Abstract : This study aimed at investigating the cytoprotective effect of an ethyl acetate extract of insect fungi against high glucose- (HG-) induced oxidative damage in human umbilical vein endothelial cells (HUVECs). An insect fungus strain termed CH180672 (CH) was found for protecting HUVECs from HG-induced damage. In this study, CH was identified as Simplicillium sp. based on a phylogenetic analysis of ITS‐rDNA sequences. Ethyl acetate extract (EtOAc) of this strain (CH) was subjected to the following experiments. Cell viability was examined with the MTT method. To evaluate the protection of CH, intracellular reactive oxygen species (ROS), malondialdehyde (MDA) levels, and the activities of antioxidant enzymes were measured and the expression of oxidation-associated proteins was assessed. In the current study, it has been found that CH can increase the survival rate of HUVECs induced by HG. Additionally, we found that HG-induced nuclear factor-erythroid 2-related factor 2 (Nrf2) and heme oxygenase 1 (HO-1) signal decreased and increased the intracellular ROS and MDA generation in HUVECs. However, CH treatment strongly promoted the translocation of Nrf2 and its transregulation on HO-1 and ultimately inhibited the high level of ROS and MDA induced by HG. The regulatory ability of CH was similar to Nrf2 agonist bardoxolone, while the effect was abolished by ML385, suggesting that Nrf2 mediated the inhibition of CH on HG-induced oxidative stress in HUVECs. Taken together, CH can improve HG-induced oxidative damage of HUVECs, and its mechanism may be related to the regulation of the Nrf2/HO-1 pathway.